Cato Guldberg and Peter Waage, the history of the Law of Mass Action, and its relevance to clinical pharmacology. (22nd October 2015) - Ferner, Robin E.; Aronson, Jeffrey K.
Abstract : We have traced the historical link between the Law of Mass Action and clinical pharmacology. The Law evolved from the work of the French chemist Claude Louis Berthollet, was first formulated by Cato Guldberg and Peter Waage in 1864 and later clarified by the Dutch chemist Jacobus van 't Hoff in 1877. It has profoundly influenced our qualitative and quantitative understanding of a number of physiological and pharmacological phenomena. According to the Law of Mass Action, the velocity of a chemical reaction depends on the concentrations of the reactants. At equilibrium the concentrations of the chemicals involved bear a constant relation to each other, described by the equilibrium constant, K . The Law of Mass Action is relevant to various physiological and pharmacological concepts, including concentration–effect curves, dose–response curves, and ligand–receptor binding curves, all of which are important in describing the pharmacological actions of medications, the Langmuir adsorption isotherm, which describes the binding of medications to proteins, activation curves for transmembrane ion transport, enzyme inhibition and the Henderson–Hasselbalch equation, which describes the relation between pH, as a measure of acidity and the concentrations of the contributory acids and bases. Guldberg and Waage recognized the importance of dynamic equilibrium, while others failed to do so. Their ideas, over 150 years old, are embedded in and still relevant to clinical pharmacology. Here we explain the ideas and in a subsequent paper show how they are relevant to understanding adverse drug reactions.